Restraint Stress Induced Hyperpermeability and Damage of the Blood-Brain Barrier in the Amygdala of Adult Rats - Xu, Guangming; Li, Yingmin; Ma, Chunling; Wang, Chuan; Sun, Zhaoling; Shen, Yiwen; Liu, Li; Li, Shujin; Zhang, Xiaojing; Cong, Bin (Frontiers in Molecular Neuroscience, 2019)
Intense or prolonged exposure to stress can damage various brain structures, including the amygdala and hippocampus, which are associated with emotional-cognitive functions. Furthermore, this deterioration has been linked to a myriad of neurodegenerative and psychiatric disorders, in particular through disruption of the blood-brain barrier (BBB) . However, insights remains scarce concerning the effects and mechanisms associated with stress on the BBB in the amygdala. This study explored the effects of restraint stress on the permeability and integrity of the BBB in the amygdala of male adult SD rats. Serum levels of corticosterone (CORT) and S100B were determined through ELISA. The permeability of the BBB was assessed by measuring Evans Blue (EB) leakage tissue samples from the rats’ amygdala. These samples were immunostained for markers of tight junctions (Claudin-5, Occludin, ZO-1) and adherens junctions (VE-cadherin), as well as GLUT-1 and AQP-4. Staining was evaluated through confocal microscopy, and the level of expression of these proteins was quantified using the Western Blot (WB) technique. The ultrastructure of brain microvascular endothelial cells was assessed with transmission electron microscopy. Moreover，interleukin-1 beta (IL-1β) content in serum and the amygdalar tissues were determined through ELISA. Exposure to restraint stress was associated with higher serum levels of S100B and EB leakage in amygdala tissues, especially in days 7, 14 and 21 of the experiment, indicating increased permeability of the BBB. After restraint stress, significant decreases in protein expression were detected for tight junctions, adherens junctions and GLUT-1, while a significant increase was observed for AQP-4. The variation trends of fluorescence intensity generally paralleled these results. Following restraint stress, transmission electron microscopy ascertained enlarged gaps in tight junction and thickened basal membranes in amygdalar capillaries. In addition, increased IL-1β contents in serum and amygdalar tissues were observed in the restraint-stressed groups. These data suggest restraint stress mediates time-dependent alterations in the permeability of the BBB, with modifications in the expression of proteins from tight junctions and adherens junctions, and ultrastructural changes in brain microvascular endothelial cells. And it was associated with the inflammation. These alterations may be associated with behavioral and cognitive dysfunctions and neurodegenerative disorders.